UMPSA continues to thrive - T.N., Alagesh (New Straits Times Press (M) Bhd., 2023)
KUANTAN: Ranked top among the Malaysian Technical University Network and in the 601-800 range in the Times Higher Education World University Rankings 2024, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) will continue to thrive in research and innovation, and offer world-class academic programmes.